Framework for Creating Successful Multidisciplinary Translational Research Teams - S Supriya; Shanthanu Patil; M Bagavandas (Indian Journal of Community Medicine)
Translational research teams are the need of the hour to address society’s complex problems. Researchers from various disciplines coordinate and collaborate to form research teams. The translation of their work from inception to social impact is integral to the team’s function. In this essay, the basic-fit translational model and design delivery framework are developed to assist researchers from all disciplines in self-analyzing their social impact to augment collaboration.